Domain-Specific Inter-textual Non-taxonomic Extraction (DSINTE) - Nur Fatin Nabila Mohd Rafei Heng; Nurlida Basir; Madihah Mohd Saudi; Mamat A.; Azmi-Murad M.A.; Mustapha N.; Deris M.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Non-taxonomic relation is one of the most important components in ontology to describe a domain. Currently, most studies focused on extracting non-taxonomic relationships from text within the scope of single sentence. The predicate between two concepts (i.e. subject and object) that appear in a same sentence is extracted as potential relation. Therefore the number of identified relations is less that what it could be and does not properly represent the domain. In this paper, we introduced a method named Domain-specific Inter-textual nontaxonomic extraction (DSINTE) to extract the non-taxonomic relations between two concepts that appear not only in a single sentence but also in different sentences. The proposed method has been illustrated using a collection of domain texts from New York Times website. Recall metrics have been used to evaluate the results of the experiments..